Between Past and Future - 1/10
Recording of the academic panel entitled “Meanings of 1989 and the Present Significance of the Past”, the second panel of the “Between Past and Future: The Revolutions of 1989 and the Struggle for Democracy in Central and Eastern Europe" international conference that was held at CEU in March 1999. The chairman of the panel is Vladimir Tismăneanu. The tape contains the final part of Sorin Anothi’s presentations and the discussion between the members of the panel and the audience that followed the individual presentations. The panel is composed of Jacques Rupnik (Institute of Political Studies, Paris), Tamás Gáspár Miklós (Georgetown University), Karol Soltan (University of Maryland), Daniel Chirot (University of Washington) and Sorin Antohi (Academic Pro-Rector at CEU).